The Effectiveness of English Learning Media through Google Classroom in Higher Education - Abd. Syakur; Sugirin; Widiarni (Britain International for Academic Research (BIAR) Publisher, 2020)
The industrial revolution's technological development, dubbed era 4.0, had a significant impact on the world of education, particularly higher education. The purpose of this study was to determine the efficacy of implementing education through teaching methods in the Covid 19 season. Online Education is one of the techniques used in blended learning. All academics at the tertiary institution participate in Teaching through blended learning. This research is a two-cycle trial, referred to as cycle I and cycle II. The results of the data are compared to the cycle of learning implementation. The results of the study describe blended learning, Google classroom as an alternative process of teaching English, and Google classroom as a process of teaching blended learning. Cycle I results are on average lower than Cycle II results in terms of learning (69 to 100 percent), active student (27 to 100 percent), accomplishments (89 to 96 percent), learning process (70 to 100 percent ), complete score (25 to 86 percent ), not complete ye (75 to 12 percent ), and success (45 percent to 75 percent ) Use of Google Classroom helps improve the average achievement of students enrolled in English education departments. The research concludes that this application is capable of operating effectively, assisting lecturers and students enrolled in English language education study programs in carrying out the learning process more intensely.